2019
DOI: 10.1007/s12094-018-02012-8
|View full text |Cite
|
Sign up to set email alerts
|

CEP55 promotes epithelial–mesenchymal transition in renal cell carcinoma through PI3K/AKT/mTOR pathway

Abstract: Purpose To study the detailed mechanisms of tumorigenesis and clinical outcomes of centrosomal protein 55 (CEP55) overexpression in renal cell carcinoma. Materials and methods Microarray analysis was performed to explore differentially expressed genes in five pairs of RCC tissues. Data of CEP55 expression and corresponding clinical information for 532 RCC patients of TCGA database were downloaded from cBioPortal. The expression of CEP55 in RCC tissues and cells was determined by real-time quantitative reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Several lines of evidence suggest that EMT promotes tumour metastasis in various cancers, including RCC [32][33][34][35][36][37]. Previous molecular analysis indicated that the high expression of AGK can induce the expression of HIF1a and promote EMT in cervical squamous carcinoma cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that EMT promotes tumour metastasis in various cancers, including RCC [32][33][34][35][36][37]. Previous molecular analysis indicated that the high expression of AGK can induce the expression of HIF1a and promote EMT in cervical squamous carcinoma cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HIF-1α previously made were used as described 41 . MLN4924 was synthesized, as described 11 . LY294002 (L9908) (a PI3K inhibitor), Rapamycin (mTOR inhibitor) and MK-2206 (s1078) (an AKT inhibitor), (Selleck Chemicals, Houston, TX, USA) were purchased from the indicated companies.…”
Section: Discussionmentioning
confidence: 99%
“…It is revealed that protein from these may also play a key role in ccRCC. The study of Chen et al (2019c) had shown that up-regulated CEP55 could promote epithelial-to-mesenchymal transition, migration, and invasion through the PI3K/AKT/mTOR pathway in RCC. Similarly, CEP55 was found to be up-regulated in multiple types of cancer and was related to unfavorable prognosis of non-small-cell lung cancer patients ( Jiang et al, 2018 ) and breast cancer patients ( Yin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%